APLIKASI KOMPOS TANDAN KOSONG KELAPA SAWIT DAN HORMON TANAMAN UNGGUL TERHADAP PERTUMBUHAN TANAMAN ANTHURIUM (Anthurium sp) - T. Rosmawaty; Samsul Kurniawan (DINAMIKA PERTANIAN, 2017)
This research aims to examine the effect of compost bunches of oil palm and plant hormone superior on growt of anthurium plant. The research was conducted at the experiment farm of faculty of agriculture Riau Islamic university during 4 months, starting from April to July 2015. The completely randomized design was used by using 2 factors, the first factor was compost bunches of oil palm, consisting of 0, 15, 30, 45 g/polybag, the second factor was plant hormone superior consisting of 0, 2, 4, 6 milli/liter. The parameters observed the number of leaves per plant, total leaf area, relative growth rate, net assimilation rate, root volume. The results showed that interactinally has effect on number of leaves per plant and root volume the best treatment of compost bunches of oil palm 30 g/ploybag and plant hormone superior 4 milli/liter. Application of compost bunches of oil palm affects all observation parameter, the best treatment 30 g/polybag. Application of plant hormone superior affects all observation parameter, the best treatment 4 mili/liter.